DDT and pyrethroid resistance in Xenopsylla cheopis (Rothschild), the Oriental rat flea in northern Uganda - Ames, Abbe D., author; Black, William C., IV, advisor; Gage, Kenneth L., advisor; McAllister, Janet C., committee member; Kondratieff, Boris C., committee member; Cole, Patricia A., committee member (Colorado State University. Libraries, 2011)
Development of insecticide resistance by vectors of disease is a well-recognized and continuous concern for public health officials. Monitoring insects for development of resistance to the chosen toxicants is part of effective management philosophy. Several programs to control mosquito vectors of malaria utilize insecticides with similar modes of action targeting the insect. Fleas can vector plague and in many areas inhabit the same environment that is the focus of mosquito management. Non-target insect development of resistance is a phenomenon most commonly associated with agriculture, but can also apply to insect vectors that threaten public health. Rapid and effective methods of monitoring for the possible development of insecticide resistance in fleas are important measures taken to prevent or suppress a plague outbreak. This study describes the development and application of a new field assay for evaluating phenotypic demonstration of insecticide resistance in fleas, results of biochemical analyses performed to evaluate possible development of metabolic detoxification pathways, and the subsequent elucidation of the para voltage gated sodium channel gene in Xenopsylla cheopis (Rothschild) with concurrent analyses of the prevalence and effects of knockdown (kdr) mutations in the gene. The field assay used a glass Petri dish coated with a dose of a chosen insecticide and a time mortality assay that was performed for 60 minutes. Discriminating concentrations, established on colony reared fleas, was tested on field collected fleas in northern Uganda. Fleas from villages with a history of indoor residual spraying (IRS) of DDT and /or pyrethroid were tested with those insecticides and significant increased survival was demonstrated. Phenotypic resistance to DDT was demonstrated with an 81.8% survivorship. Lambda-cyhalothrin tested fleas from three villages demonstrated phenotypic resistance of levels of 57.7%, 60.5%, and 58% survivorship. Enzyme profiles indicated increased levels of expression of α-esterase and β-esterase in field caught fleas compared to colony-reared fleas. Fleas potentially exposed to DDT and/or pyrethroids had higher levels than did unexposed fleas. An increase in insensitive acetylcholinesterase was found in fleas from villages with no known history of IRS. No increase in glutathione S-transferase was noted in any population. The para voltage gated sodium channel gene for X. cheopis was amplified and sequences for colony and Ugandan fleas were analyzed with emphasis on knockdown resistance (kdr) evolution in the fleas. Extensive evidences of selective pressures influencing genetic profiles of kdr development faster than expected for random mutation or recombination were found. The phenylalanine allele, associated with kdr, was found at an average of 95.1% frequency in villages with an IRS history. Field caught fleas with no known insecticide exposure had an allele frequency of 13.3%. All three studies clearly indicate resistance is developing quickly in Ugandan flea populations and should be addressed with surveillance and management.
Keywords: fleas; bioassay; insecticide resistance; kdr; plague; Uganda